Comprehensive Material Characterization and Seismic Performance Evaluation of a Traditional Masonry Residential Building with Reinforced Concrete Slabs - Basak Boduroglu Yazici; Oguz Uzdil (Buildings)
Reinforced concrete began replacing traditional masonry construction in the early 20th century, yet hybrid buildings combining unreinforced masonry (URM) walls with concrete slabs remain prevalent in Istanbul. Understanding their seismic behavior is critical for risk mitigation and heritage preservation. This study investigates a seven-story masonry residential building with cast-in-place reinforced concrete slabs constructed in 1953. The assessment involved non-destructive inspections, double flat-jack and shear tests, and geophysical site surveys. A finite element model was developed using Midas Gen software v2020 and analyzed through linear response spectrum and nonlinear pushover analyses based on TBSC-18 and SRMGHS-17. The modulus of elasticity ranged from 200.2 MPa to 1062.2 MPa, and bed joint shear strength varied between 0.50 MPa and 0.79 MPa. The building satisfied inter-story drift criteria for limited damage (SL-3), controlled damage (SL-2), and pre-collapse (SL-1). However, it failed to meet the shear force requirements at all levels. Pushover analysis revealed ultimate lateral capacities of 11,997 kN in the x-direction and 16,209 kN in the y-direction. The findings highlight the shear vulnerability of such hybrid systems and underscore the importance of combining experimental characterization with numerical modeling to develop effective retrofitting strategies.